The Factors that Influence Customer Purchase Intention: The Tale of Zalora Malaysia - Lu Man Hong; Pillo Anak Alisliza Perak (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
Since Zalora Malaysia was designated as the top fashion specialised online retailer based on iPrice's Map of e-commerce, this study was done to investigate the factors that impact consumer buying intention in Zalora Malaysia. As a result, brand image, site design, and service quality are the independent variables for those elements. The intention to buy among Zalora Malaysia clients is the dependent variable of this study. Furthermore, the goal of this research is to look at the interaction between elements that impact customers' purchasing intentions in Zalora Malaysia. To confirm the research hypothesis, the researcher gathered 237 responses via a google form created by the researcher and distributed them online to any Malaysian citizen who only purchased from Zalora Malaysia and answered the questionnaire in general via Facebook or Instagram to obtain respondents aged 21 to 50 years and above. Only one hypothesis is validated and approved in this research study, according to the findings, and it is connected to the relationship between site design features and purchase consumers in the Zalora Malaysia application. The brand image and service quality elements that impact customers' purchasing intentions in the Zalora Malaysia application are two hypothetical relationship factors that are not approved and have no value. In the Zalora Malaysia application, this reveals simply the site design variables that are important and the link between client purchase intents.